Family Limitation - Sanger, Margaret, 1879-1966 (London : Bakunin Press, 1920)
1920 1920 1920s 16 pages : illustrations FAMILY LIMITATION. 3 INTRODUCTION. The need for information concerning birth control is more urgent to-day among the working women of Europe than it has ever been before. The world war has awakened us to the realisation that governments will continue to plunge nations into wars just so long as we, the mothers of men, make life cheap. It is the big battalions of unwanted babies that make life so hard for the working woman and keep her in poverty and stress from generation to generation. Every mother feels the wrong that the State imposes upon her when it deprives her of information to prevent the bringing into the world of children she cannot feed or clothe or care for. She resents this with all the bitterness of her strength and will rejoice to find some information contained herein, to help the mothers free themselves from the burden of too frequent pregnancies. I have tried to give the knowledge of the best French and Dutch physicians translated into the simplest English, that all may easily understand. There are various and numerous mechanical means of prevention which I have not mentioned here, mainly because I have not come into personal contact with those who have used them or could recommend them as entirely satisfactory. I feel there is sufficient information given here, which, if followed, will prevent a woman from becoming pregnant unless she desires to do so. If a woman is too indolent to wash and cleanse herself, and the man too selfish to consider the consequences of the act, then it will be difficult to find a preventive to keep the woman from becoming pregnant. Of course, it is troublesome to get up to douche, it is also a nuisance to have to trouble about the date of the menstrual period. It seems inartistic and sordid to insert a pessary or a suppository in anticipation of the sexual act. But it is far more sordid to find yourself several years later burdened down with half a dozen unwanted children, helpless, starved, shoddily clothed, dragging at your skirt, yourself a dragged out shadow of the woman you once were. Don't be over sentimental in this important phase of hygiene. The inevitable fact is that unless you prevent 15X/2/490/4